Types of Acari in the Collection at Museo de La Plata, Argentina - Salazar Martínez, Ana Ernestina (2004)
The 333 type specimens of Acari housed at the Museo de La Plata (División Entomología), Argentina, were examined and listed, providing updated information on categories of types, data of collection and hosts. The types belong to 21 species and one subspecies described by the following authors Alzuet & Abrahamovich (5), Alzuet & Brandetti (3), Alzuet & Delgado (1), Alzuet & Mauri (2), Alzuet, Cicchino & Abrahamovich (2), Bischoff de Alzuet (4), Mauri & Alzuet (5).